SAT0442 Which AEs of Biological Therapy Led to Discontinuation of Treatment in an Open Monocentric Long-Term Prospective Study of 377 JIA Patients. (23rd January 2014) - Pontikaki, I.; Romano, M.; Gattinara, M.; Salmaso, A.; Meroni, P.; Gerloni, V.
Abstract : Objectives: To report adverse events (AEs), which led to discontinuation of biologics, in a large cohort of patients with juvenile idiopathic arthritis (JIA) treated with biological therapy (BT). Methods: All patients with JIA, non responder or intolerant to DMARDs, treated with BT at the pediatric Rheumatologic Centre of the G Pini Institute (Milan, Italy) from November 1999 to November 2012, were enrolled in an open, single-centre, long-term prospective study. All AEs were recorded on a unique registration form. Results: 377 pts (208 etanercept, 89 infliximab, 55 adalimumab, 5 golimumab, 2 certolizumab, 9 abatacept, 7 anakinra, 2 rituximab) were enrolled. Median onset age was 5.8 yrs (mean 6.9, range 0.4-18.0). Median disease duration was 7.5 yrs (mean 9.2, range 0.2-41.4). Median period of follow-up was 5.5 yrs (mean 5.6, range 0-12.7). A total of 220 (58.4%) pts (110 etanercept, 77 infliximab, 25 adalimumab, 5 abatacept, 3 anakinra) failed to respond to or did not tolerate the first therapy and 149 (39.5%) switched to a second one. A total 750 courses of BT (634 anti-TNF, 57 anti-IL-1ra and 59 anti-cells treatments) were administered; 157 (20.9%) AEs occurred and the frequency was 0.09 AEs/patient/year. Infusion reactions led to discontinuation in 38 (24.2%) courses and were the most common AEs in our pts treated with infliximab. The most frequent AEs occurred in pts with JIA on etanercept were important behavioural alterations (depression, anxiety, aggressiveness). One case of hypoglossal paralysis and 2 suspected demielinating disease were reported. New onset of inflammatory bowel disease (9 etanercept and 1 adalimumab) and new onset or flare-up of chronic iridocyclitis (15 etanercept, 1 infliximab, 1 certolizumab) were also reported. Dermatological AEs occorred in 15 (9.6%) courses, most of them were recorded in adalimumab. 9 (6%) cases of injection site reaction were also described. Conclusions: In our 13-year, study BT were well tolerated and safe; most of AEs reported were reversible by discontinuation of therapy. In case of active disease it was necessary to switch to another biological agent. Children and young adults affected by JIA should be carefully monitored so as to limit the risk of AEs during BT as much as possible. Disclosure of Interest: None Declared